Analysis of Data Management in Sigi District Statistics Center - Anjung Budi Cahyono; Rajindra Rajindra; Haris Abd. Kadir (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
This study aims to determine data management on the gross regional domestic product at the Central Bureau of Statistics of Sigi Regency. Management of Sigi Regency Gross Regional Domestic Product data shows several uses of the final product manifested in the form of "final demand." The final demand referred to consists of components of household final consumption expenditure (PK-RT), final consumption expenditure of non-profit institutions serving households (PK-LNPRT), government final consumption expenditure (PK-P), gross fixed capital formation ( PMTB), Changes in Inventory (PI), as well as components of exports of goods and services.